Ownership and care in culturally significant architecture: three case studies - Bosman, Gerhard (University of the Free State, 2017)
Public buildings are not permanent, but at most durable and robust enough to outlast a few generations. Earth-constructed buildings, as soft architecture used for public buildings, need more care and maintenance than buildings in brick, stone, concrete and steel. The ownership and care of private and public buildings reflect social attitudes and sustainable means. The attitudes towards the durability and technical performance of building materials can lead to the rejection of earth architecture, due to the high maintenance required. Negative attitudes discourage the use of traditional earth-constructed buildings in Africa. Case studies show the ownership and care in maintenance as temporal reflectors of the communal well-being. This care or no care becomes a celebration or rejection of the built environment. The argument is that, without ownership, public buildings constructed in conventional building materials can deteriorate faster than well-accepted maintained earth-constructed buildings of cultural significance. This phenomenon should be considered if public buildings are built in contemporary earth construction.
Keywords: Attitudes; Cultural significant architecture; Earth architecture; Temporal ownership